Pengaruh Kecerdasan Spiritual terhadap Disiplin Belajar Santri di Madrasah Diniyyah - Rizal Fathurrohman; Ibrahim Ibrahim (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2021)
This research aims to determine the effect of spiritual intelligence on the learning discipline of students at Madrasah Diniyyah. After testing, it can be concluded that spiritual intelligence partially has an influence on the learning discipline of students. Meanwhile, spiritual intelligence has a simultaneous influence on the students’ learning discipline. Based on the statistical test, the author got an R squared value of 0.942 or 94.2% which explains that 94.2% of the learning discipline variable transition can be explained by the spiritual intelligence variable, while the remaining 5.8% is explained by other variables outside the model. The score of 0.942 explains that there is a strong and unidirectional relationship between the independent variable and the dependent variable simultaneously. Based on the t-test, it was found that spiritual intelligence had no influence on the student’s learning discipline. For the F test, it was found that simultaneously spiritual intelligence had an influence on the learning discipline of students at Madrasah Diniyyah Al Munawwir Krapyak, Yogyakarta.